Justification of early neurorehabilitation in neonates - L.P. Badogina; O.Yu. Obolonskaya; V.A. Kondratiev; M.V. Shirikina (Zaslavsky O.Yu., 2017)
Background. The problem of disabled children in Ukraine is of special significance as a result of the constant growth of their number among the peadiatric population. Currently, many premature neonates and children with inoperable malformations are nursed in the neonatal intensive care unit (NICU). At the same time, the increase of clinical cases of chronic and associated pathology of the nervous system leads to deepening the process of disability in peadiatric population. Today, the primary need is neurorehabilitation of children, but many questions are still not resolved. When should we begin rehabilitation of a child with one or another pathology? Who should conduct this process? How intensive could it be? What are the goals and objectives in this case? The purpose of the study was to highlight the need for early neurorehabilitation of newborns already in the first days of life, at the stage of the NICU. Also, to evaluate the effectiveness of a set of measures for primary neonatal rehabilitation in the nursing stage according to the Alberta Infant Motor Scale (AIMS) during the first year of child's life. Materials and methods. Neurorehabilitation according to the developed method was carried on in neonates with pathology of nervous the nervous system who received treatment in the nursing department of NICU. Rehabilitation activities were conducted with the participation of nurses, neonatologists, physical therapists with the involvement of mothers of sick children. Twenty-five patients who underwent ventricular bypass surgery were monitored. Among them - 12 children with malformations of the spinal cord (spina bifida) and 13 - with posthemorrhagic hydrocephalus. The examined group included 18 patients who underwent neurorehabilitation according to the developed method. The control group consisted of 7 children treated only with massage. To evaluate the effectiveness of a set of exercises, AIMS was used during the first year of child's life. Results. The patients of the examined group had classes with a set of activities. There were exercises on the development of communication skills: constant communication with the child controlling eye contact; palmar gymnastics for the prevention of spasticity, the development of grasping reflex, exercises to prevent strabismus, to develop strength of the muscles of the hands, neck and back according to the tummy time system; exercises to prevent contractures in children with partially preserved function of the lower extremities. During the stay in the NICU, sessions were conducted by medical personnel, and later - by the parents of the child, after they were trained. Motor skills and communicative abilities were assessed dynamically, throughout the year, after the transfer of children from the intensive care unit to the neurosurgical department and at the outpatient stage. In patients from the control group who weren't treated with this set of exercises, reflexes faded as a result of an increase in the tone of the muscles of the wrists with the development of flexion contractures; decreased ability to concentrate, development of persistent strabismus. One patient from the examined group was transferred to another department and didn't continue this rehabilitation course. The patients from the control group were also examined dynamically, throughout the year. In comparison, in children of the main group, the average score of the AIMS scale at the end of the year of observation was 19 points, and in children from the control group - only 9 points. Conclusions. Pattients with pathology of the nervous system require an integrated, continuous and long-lasting rehabilitation process, which should begin as early as possible, even in the NICU after intensive care procedures, continue in the nursing ward for newborns and in the future - outpatiently. The proposed individual rehabilitation program with a set of exercises depending on the needs of the child and his/her capabilities gives a significant positive result regarding the formtion of the motor and sensory skills of the child and preventing their extinction. The Alberta Infant Motor Scale is convenient and informative for evaluating the motor development of children with pathology of the nervous system aged 0 to 12 months.